2013
DOI: 10.3390/ijms140611024
|View full text |Cite
|
Sign up to set email alerts
|

Chemoresistance Is Associated with MUC1 and Lewis y Antigen Expression in Ovarian Epithelial Cancers

Abstract: ObjectiveThe aim of this study was to analyze the correlation and clinical significance between the expression of Mucin-1 (MUC1) and the Lewis y antigen with chemoresistance in ovarian epithelial cancers.MethodsOvarian cancer patients (n = 92) treated at our hospital from May 2005 to July 2009 were divided, according to their treatment and follow-up outcomes, into a resistant group (n = 37) or sensitive group (n = 55). The expression of MUC1 and Lewis y antigen in ovarian cancer tissues was detected using immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…MUC1 protein level is significantly increased in platinum resistant ovarian tumors compared to those in sensitive-group because of chromosomal amplifications of 1q21-q22 [52]. A follow-up analysis of 92 ovarian cancer patient cohort also showed that the increase of MUC1 expression is a significant risk factor for chemoresistance to taxane combined platinum-based drugs in patients with ovarian epithelial cancer [53].…”
Section: Non-mucinous Tumorsmentioning
confidence: 95%
“…MUC1 protein level is significantly increased in platinum resistant ovarian tumors compared to those in sensitive-group because of chromosomal amplifications of 1q21-q22 [52]. A follow-up analysis of 92 ovarian cancer patient cohort also showed that the increase of MUC1 expression is a significant risk factor for chemoresistance to taxane combined platinum-based drugs in patients with ovarian epithelial cancer [53].…”
Section: Non-mucinous Tumorsmentioning
confidence: 95%
“…Desmoplastic growth provides tumors a unique environment that favors growth and expansion along with resistance against chemotherapy [95]. Multiple studies suggest a direct role of MUC1 in facilitating desmoplasia and chemoresistance [9698]. At a metabolic level, MUC1 expression leads to metabolite secretions that are known to facilitate stromal cell metabolism, growth, and/or recruitment.…”
Section: Therapeutic Implications Of the Metabolic Functions Of Muc1mentioning
confidence: 99%
“…MUC1‐C, a single‐pass transmembrane protein, can interact with vascular endothelial growth factor (VEGF), early growth factor receptor (EGFR), and others (Kufe, ). The increased expression of MUC1 was a significant risk factor for chemoresistance in ovarian epithelial cancer and contributed to resistance to trastuzumab in breast cancer cells via activation of the HER2 pathway (Raina et al, ; Zhang et al, ). In non‐small cell lung cancers, elevated expression of MUC1 was related with stemness and paclitaxel resistance.…”
Section: Discussionmentioning
confidence: 99%